How can the word "NEW" evoke consumers' experiences of novelty and interest?. (July 2016) - Sung, Billy; Hartley, Nicole; Vanman, Eric; Phau, Ian
Abstract: This paper examines the role advertising cues play in inducing subjective perceptions of product novelty and how they can evoke consumer interest toward an advertisement. Specifically, it uses behavioral and psychophysiological measures to: (1) investigate the effect of novelty cues on consumers' subjective appraisal of novelty; (2) demonstrate that novelty cues may evoke the emotion of interest; and (3) differentiate the effect of the emotion of interest on liking and arousal. Across two experimental studies, we demonstrated that simply adding the word "new" in an advertisement increases behavioral (i.e., viewing duration) and psychophysiological responses (i.e., cardiac activity) of interest. However, the word "new" did not evoke liking and arousal. This suggests that novelty cues in an advertisement will make the consumers perceive the product to be novel and further evoke consumer interest. Highlights: This paper uses behavioral and psychophysiological measures to demonstrate that adding the word "new" in an advertisement will enhance consumers' perception of product novelty and evoke interest. It eliminates potential alternative explanations by showing that the novelty cue effect evokes interest but not liking, and arousal. The current research provides novel insights into the effect of consumers' subjective perception of product newness on interest and extends the current literature that has commonly defined product newness as the objective difference in the product's functional attribute.